2021
DOI: 10.1080/01612840.2021.1956657
|View full text |Cite
|
Sign up to set email alerts
|

Brief Admission for Patients with Self-Harm from the Perspective of Outpatient Healthcare Professionals

Abstract: Acknowledgments: Many thanks go to the outpatient staff in this southern Swedish region, who participated in this study and were generous in contributing their knowledge and perspective during the interviews. Also thanks to Anchor English for proofreading the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Increased patient responsibility and care at an early stage can thus be perceived as significant and helpful factors from the perspective of both the patient (Eckerström et al, 2020; Enoksson et al, 2021), healthcare staff (Arnold et al, 2021; Eckerström et al, 2019) and, as found in this study, relatives. Relatives in this study said that they promote the patient's ability to take responsibility for, and be observant of, early signs of deterioration, in that it is the patient who has control over enrollment and discharge, which has also emerged in other studies (Ellegaard et al, 2017; Enoksson et al, 2021; Helleman et al, 2014a, 2014b).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Increased patient responsibility and care at an early stage can thus be perceived as significant and helpful factors from the perspective of both the patient (Eckerström et al, 2020; Enoksson et al, 2021), healthcare staff (Arnold et al, 2021; Eckerström et al, 2019) and, as found in this study, relatives. Relatives in this study said that they promote the patient's ability to take responsibility for, and be observant of, early signs of deterioration, in that it is the patient who has control over enrollment and discharge, which has also emerged in other studies (Ellegaard et al, 2017; Enoksson et al, 2021; Helleman et al, 2014a, 2014b).…”
Section: Discussionmentioning
confidence: 55%
“…In addition, it is considered of great importance to avoid a deteriorating mood that can lead to the patient being exposed to risks. BA is also referred to as a tool for preventing suicide attempts (Arnold et al, 2021). The fear that the patient will hurt themselves or take their own life during a deterioration is something that recurs among relatives in this study, and access to BA therefore contributed to relief.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feeling safe was cited as a major benefit of access to BA, also among non-users. Results from studies on BA for adults have implied a similar value of the BA contract, providing safety also outside of hospital and offering a beneficial complement to ongoing outpatient care [ 15 , 18 , 40 ]. However, adolescents in this study also reflected upon BA as potentially risky, which may be compared to adults ‘feeling lost and loose’ on BA [ 18 ].…”
Section: Discussionmentioning
confidence: 99%